RELATIVE TECHNICAL EFFICIENCY OF CALIFORNIA LEMON FARMING IN BANYUMAS REGENCY - Muhammad Alfin Hisam; Dindy Darmawati Putri; Altri Mulyani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
This research aims to determine the efficiency and relative technical inefficiency of lemon farming in Banyumas Regency. The background of this research is the need for self-sufficient lemon production and the existence of several issues in the management of production inputs in lemon farming. This is quantitative research with a population of 9 lemon farmers in Banyumas Regency. All 9 farmers were used as samples, employing a saturation sampling technique. Data for this research were collected through questionnaires. The data analysis in this research utilized Data Envelopment Analysis (DEA) with an input-oriented approach. The results of this research indicate that the use of production inputs needs to be adjusted among Decision Making Units (DMU) to achieve optimization.